Combination of modeling and experiment in structure analysis of intercalated layer silicates - Capková, Pavla; Pospísil, Miroslav; Weiss, Zdenek (Journal of molecular modeling, 2003)
A strategy for the structure analysis of intercalated layer silicates based on a combination of modeling (i.e. force field calculations) and experiment is presented. Modeling in conjunction with experiment enables us to analyze the disordered intercalated structures of layer silicates where conventional diffraction analysis fails. Experiment plays a key role in the modeling strategy and in corroboration of the modeling results. X-ray powder diffraction and IR spectroscopy were found to be very useful complementary experiments to molecular modeling. Molecular mechanics and molecular dynamics simulations were carried out in the Cerius2 and Materials Studio modeling environments. An overview is given of the structures of layer silicates, especially smectites intercalated with various inorganic and organic guest species. Special attention is paid to the ordering of guests in the interlayer space, as it is important for the practical applications of these intercalates, where the interlayer porosity, photofunctions, etc. must be controlled. Figure Structure of montmorillonite intercalated with octadecylamine via ion-dipole interaction with the maximum concentration of guests corresponding to the monolayer arrangement of guests with basal spacing 33.3 A. The Na cations remaining in the interlayer are visualized as pink balls
Keywords: molekulární struktura; molekulární modely; Molecular Structure; Silicates; Spectrophotometry, Infrared; Models, Molecular; silikáty; spektrofotometrie infračervená; Rhodamines; X-Ray Diffraction; difrakce rentgenového záření; rhodaminy